Vitamin D Can Ameliorate Chlorhexidine Gluconate-Induced Peritoneal Fibrosis and Functional Deterioration through the Inhibition of Epithelial-to-Mesenchymal Transition of Mesothelial Cells. (1st October 2015) - Lee, Yi-Che; Hung, Shih-Yuan; Liou, Hung-Hsiang; Lin, Tsun-Mei; Tsai, Chu-Hung; Lin, Sheng-Hsiang; Tsai, Yau-Sheng; Chang, Min-Yu; Wang, Hsi-Hao; Ho, Li-Chun; Chen, Yi-Ting; Wu, Ching-Fang; et al.
Abstract : Background . Peritoneal dialysis (PD) can induce fibrosis and functional alterations in PD patients' peritoneal membranes, due to long-term unphysiological dialysate exposure, partially occurring via triggering of epithelial-to-mesenchymal transition (EMT) in peritoneal mesothelial cells (MCs). Vitamin D can ameliorate these negative effects; however, the mechanism remains unexplored. Therefore, we investigated its possible links to MCs EMT inhibition. Methods . Peritoneal fibrosis was established in Sprague-Dawley rats by chlorhexidine gluconate (CG) intraperitoneal injection for 21 days, with and without 1 α, 25(OH)2 D3 treatment. Morphological and functional evaluation and western blot analysis of EMT marker were performed upon peritoneum tissue. In vitro study was also performed in a primary human peritoneal MC culture system; MCs were incubated with transforming growth factor- β 1 (TGF- β 1) in the absence or presence of 1 α, 25(OH)2 D3 . EMT marker expression, migration activities, and cytoskeleton redistribution of MCs were determined. Results . 1 α, 25(OH)2 D3 ameliorated CG-induced morphological and functional deterioration in animal model, along with CG-induced upregulation of α -SMA and downregulation of E-cadherin expression. Meanwhile, 1 α, 25(OH)2 D3 also ameliorated TGF- β 1-induced decrease in E-cadherin expression, increase in Snai1 and α -SMA expression, intracellular F-actin redistribution, and migration activity in vitro . Conclusion . 1 α, 25(OH)2 D3 can ameliorate CG-induced peritoneal fibrosis and attenuate functional deterioration through inhibiting MC EMT.